Pathophysiology, Evaluation and Management of Metabolic Acidosis - Tinawi, Mohammad (Archives of Clinical and Biomedical Research, 2021)
Metabolic acidosis is a reduction in blood pH due to a primary reduction in serum bicarbonate (HCO3−). It is associated with a secondary reduction in carbon dioxide arterial pressure (PaCO2). Metabolic acidosis can be acute or chronic. Acute metabolic acidosis results from excess organic acids as in lactic acidosis, while chronic metabolic acidosis reflects reduced renal acidification. Metabolic acidosis is further classified into anion-gap (AG-MA) and hyperchloremic (normal anion-gap [NAG-MA]) based on serum anion gap (AG). Metabolic acidosis has adverse effects on a variety of body functions. Although base administration is helpful in the management of chronic metabolic acidosis, it is controversial in acute metabolic acidosis. Treatment of the underlying cause is the cornerstone of the management of acute metabolic acidosis.